SYSTEM OF AUTOMATIC CONTROL OF THE LEVEL OF STEAM POWER GENERATORS ON THE BASIS OF THE REGULATION CIRCUIT WITH SMOOTHING OF THE SIGNAL - Umurzakova, Dilnoza (IIUM Engineering Journal, 2020)
The purpose of this article is to develop high-quality combined automatic control systems (ACS) for the water level in the drum of steam boilers of thermal power plants (TPPs), which can significantly improve the quality of regulation and increase the efficiency of TPPs in a wide range of load changes. To improve the quality of water level control in the drum of steam generators of nuclear power plants with a pressurized water-cooled power reactor (PWPR), it is proposed to use a combined automatic control system based on a control loop with a correcting PI-controller tuned to a symmetrical optimum, with smoothing the reference signal and device compensation of the most dangerous internal and external measurable disturbances. A technique has been developed for assessing the impact of changes in the quality characteristics of transients of combined self-propelled guns by the water level in the drum of steam boilers and steam generators on the safety, reliability, durability, and efficiency of thermal power equipment of thermal power plants. Comparison was made of direct indicators of the quality of three ACS (typical and three-pulse, digital system with an observer state, and the proposed combined ACS). The simulation results of transients of the proposed and typical three-pulse self-propelled guns confirmed the advantages of the first. ABSTRAK: Artikel ini bertujuan bagi membina sistem kombinasi automatik (ACS) berkualiti tinggi bagi aras air dalam drum dandang stim tenaga terma logi kuasa (TPP). Ini dapat meningkatkan mutu peraturan dan meningkatkan kecekapan TPP secara signifikan dengan pelbagai perubahan beban. Bagi meningkatkan kualiti kawalan aras air dalam drum penjana wap loji kuasa tenaga nuklear dengan reaktor berpendingin air bertekanan (PWPR). Gabungan sistem kawalan automatik berdasarkan gelung kawalan dengan pembetulan PI telah dicadangkan dan diselaraskan simetri secara optimum, dengan melancarkan isyarat rujukan dan pembetulan peranti dari gangguan yang boleh diukur dari dalam dan luar. Satu teknik telah dibina bagi menilai kesan perubahan ciri kualiti transien gabungan berjentera pada aras air di tong dandang stim dan drum penjana wap pada keselamatan, kebolehpercayaan, ketahanan dan kecekapan peralatan tenaga terma loji janakuasa. Perbandingan dibuat pada kualiti tiga ACS (sistem digital khas dan tiga signal dengan keadaan pemerhati dan gabungan ACS yang dicadangkan). Hasil sistem simulasi transien yang dicadangkan dan tiga signal biasa berjentera mengesahkan kelebihan pada yang pertama.